Dual-purpose tunnel oxide passivated contact on silicon photoelectrodes with high photovoltages for tandem photoelectrochemical devices enabling unassisted water splitting. Issue 8 (27th January 2023) - Moon, Choongman; Alves Martinho, Filipe Mesquita; Jung, Gihun; Koh, Jaehyuk; Assar, Alireza; Nam, Sung-Wook; Canulescu, Stela; Shin, Byungha
Abstract : Tunnel-oxide-passivated contact on a crystalline Si improves the photovoltage of Si photoelectrode to reach 640–650 mV even after a high-temperature process up to 600 °C, which makes it useful as the bottom cell of a monolithic tandem device. Abstract : A tandem photoelectrochemical (PEC) water-splitting device for solar hydrogen production consists of two light absorbers with different bandgaps. Silicon photoelectrodes have been widely investigated as the low bandgap bottom cells of tandem devices because of their bandgap (1.12 eV). Herein, we apply a tunnel oxide passivated contact (TOPCon) on the front and back sides of a Si wafer to prepare a TOPCon Si PEC device. Because TOPCon has a SiO2 tunnel oxide layer providing superior surface passivation and working as a diffusion-blocking layer, TOPCon Si photoelectrodes exhibit superior photovoltage and thermal stability. Both photocathode and photoanode are tested over a broad pH range (0–14) and demonstrate high photovoltages of 640–650 mV under 1 sun illumination and excellent thermal stability by enduring a high processing temperature of up to 600 °C for 1 h in air. These advantages of TOPCon Si would provide high efficiency and great design flexibility for monolithic tandem cells. As a preliminary demonstration of the tandem integration, we test two wired tandem PEC devices based on earth-abundant materials, which are a BiVO4 photoanode–TOPCon Si photocathode and halide perovskite photocathode–TOPCon Si photoanode. These devices show STH conversion efficiencies of 0.24 and 3.6%, respectively.